The intensity of the transcriptional response varies across infection with distinct viral strains in an insect host - Allyson M. Ray; Anja Tehel; Jason L. Rasgon; Robert J. Paxton; Christina M. Grozinger (BMC Genomics)
Abstract Organisms respond to infectious agents through diverse immune strategies, and may need to cater a specific response to distinct pathogen challenges, such as various strains of a virus, to maximize fitness. Deformed wing virus (DWV) is one of the most damaging viruses of honey bees (Apis mellifera) across the globe, with variant DWV-B currently expanding at the expense of variant DWV-A. While previous research has characterized general host transcriptomic responses to viral exposure, host responses to different DWV strains have not been fully explored. Here, we performed experimental infections with the two dominant strains of DWV, A and B, as well as a mixed infection, and conducted transcriptomic analyses to compare differences in host molecular response to infection. We confirmed canonical anti-viral response to DWV infection, including upregulation of Toll pathway genes and the antimicrobial peptides abaecin and hymenoptaecin. Furthermore, our results suggest a potential role of aerobic glycolysis during viral infection in honey bees. DWV-A and mixed infections were associated with differential expression of a much larger number of host genes than infection with DWV-B. That DWV-B potentially elicits a reduced host immune response may provide a mechanistic explanation for its higher virulence and global emergence. Overall, this study provides the first evidence for strain-specific immune responses to DWV infection, and integrates these findings into the broader domain of insect immunity and host-pathogen dynamics.